Solid Organ Transplantation From Hepatitis B Virus–Positive Donors: Consensus Guidelines for Recipient Management*. Issue 5 (23rd February 2015) - Huprikar, S.; Danziger‐Isakov, L.; Ahn, J.; Naugler, S.; Blumberg, E.; Avery, R. K.; Koval, C.; Lease, E. D.; Pillai, A.; Doucette, K. E.; Levitsky, J.; Morris, M. I.; et al.
Abstract : Use of organs from donors testing positive for hepatitis B virus (HBV) may safely expand the donor pool. The American Society of Transplantation convened a multidisciplinary expert panel that reviewed the existing literature and developed consensus recommendations for recipient management following the use of organs from HBV positive donors. Transmission risk is highest with liver donors and significantly lower with non‐liver (kidney and thoracic) donors. Antiviral prophylaxis significantly reduces the rate of transmission to liver recipients from isolated HBV core antibody positive (anti‐HBc+) donors. Organs from anti‐HBc+ donors should be considered for all adult transplant candidates after an individualized assessment of the risks and benefits and appropriate patient consent. Indefinite antiviral prophylaxis is recommended in liver recipients with no immunity or vaccine immunity but not in liver recipients with natural immunity. Antiviral prophylaxis may be considered for up to 1 year in susceptible non‐liver recipients but is not recommended in immune non‐liver recipients. Although no longer the treatment of choice in patients with chronic HBV, lamivudine remains the most cost‐effective choice for prophylaxis in this setting. Hepatitis B immunoglobulin is not recommended. Abstract : A multidisciplinary panel of experts from AST reviews the literature regarding the use of organs from donors who test positive for hepatitis B virus, and provides recommendations for their use in liver, kidney, heart, and lung transplant recipients.